X-ray Thomson scattering diagnostics of impact ionization in laser-driven carbon foils. (28th June 2015) - Sperling, P; Zastrau, U; Toleikis, S; Glenzer, S H; Redmer, R
Abstract We have studied the light–matter interaction of ultra-short, intense optical laser fields with thin carbon foils via particle-in-cell simulations. Especially, the influence of additional impact ionization on the density and temperature of the generated plasma and on the corresponding Thomson scattering spectra was investigated. We predict a pump–probe experiment at the free electron laser FLASH in order to verify the importance of this effect in the laser–matter interaction on ultra-short time scales and to check our predictions quantitatively.